The Benefits and Risks of Prophylactic Central Neck Dissection for Papillary Thyroid Carcinoma: Prospective Cohort Study. (13th July 2015) - Lee, Doh Young; Oh, Kyoung Ho; Cho, Jae-Gu; Kwon, Soon-Young; Woo, Jeong-Soo; Baek, Seung-Kuk; Jung, Kwang-Yoon
Abstract : Objectives . This study evaluated the benefits of performing prophylactic central neck dissection (CND) with total thyroidectomy (TT) in management of papillary thyroid carcinoma (PTC) patients who were clinically node-negative at presentation. Methods. A total of 257 patients with stage T1 or T2 PTC and without preoperative evidence of lymph node involvement (N0) were enrolled in this prospective study. The patients were randomly assigned to two groups: (1) a total thyroidectomy (TT) group (n = 104 ) or (2) a TT plus CND group (n = 153 ). The two groups were compared for their perioperative data, complication rates, disease recurrence rates, and clinical outcomes. Results . The two groups of patients were similar in age, sex ratio, follow-up duration, and tumor size (P = 0.227, 0.359, 0.214, and 0.878, resp.). The two groups showed similar rates of disease recurrence (3.9% in the TT group versus 3.3% in the TT plus CND group); however, complications occurred more frequently in the TT plus CND group; especially transient hypocalcemia (P = 0.043 ). Conclusions. Patients treated with TT plus CND had a higher rate of complications with similar recurrence rate. We believe that CND may not be routinely recommended when treating patients with PTC.